Apobec-1 complementation factor regulates cell migration and apoptosis through Dickkopf1 by acting on its 3′ untranslated region in MCF7 cells - Xin Yan; Qianyin Li; Dongsheng Ni; Yajun Xie; Qingling He; Qianya Wan; Yamin Liu; Zhongshi Lyu; Zhaomin Mao; Qin Zhou (Tumor Biology)
A1CF (apobec-1 complementation factor) acts as a component of the apolipoprotein-B messenger RNA editing complex. Previous researches mainly focused on its post-transcriptional cytidine to uridine RNA editing. However, few study reported its role in progression of breast carcinoma cells. Wound healing assay and flow cytometry were applied to detect the migration and apoptosis; western blot, real-time polymerase chain reaction, and dual-luciferase assays were applied to investigate the potential regulation mechanism of A1CF-mediated cell migration and apoptosis. Knockdown of A1CF decreased cell migration and enhanced cell apoptosis in MCF7 cells in vitro. Western blot analysis showed that knockdown of A1CF decreased Dickkopf1 but increased c-Myc and β-catenin expression, and overexpression of A1CF can get opposite results. Knockdown of Dickkopf1 in A1CF-overexpressed cells decreased cell migration and enhanced cell apoptosis compared with A1CF-overexpressed cells. Luciferase-fused 3′ untranslated region of human Dickkopf1 activity was highly upregulated in A1CF-overexpressed MCF7 cells, but this upregulation can be inhibited by mutating conserved binding motifs of Dickkopf1 3′ untranslated region. A1CF played a crucial role in cell migration and survival through affecting 3′ untranslated region of Dickkopf1 to upregulate its expression in MCF7 cells.